A comprehensive evaluation of selected components and processes used in the manufacture of cigarettes: approach and overview. (12th December 2013) - Oldham, Michael J.; Coggins, Christopher R. E.; McKinney, Willie J.
Abstract: Context : In addition to tobacco and cigarette ingredients, there are many non-tobacco components and processes used to manufacture commercial cigarettes. Proposed cigarette components and manufacturing process changes were evaluated using a tiered toxicological testing program. Objective : The toxicological testing and evaluation of proposed changes to selected non-tobacco cigarette components and manufacturing processes are described in this special report. Materials and methods : Selected non-tobacco cigarette components and manufacturing processes were evaluated using experimental and control cigarettes. These experimental cigarettes were evaluated using mainstream smoke chemistry, bacterial mutagenicity and cytotoxicity assays. In some evaluations, 90-day nose-only mainstream smoke inhalation studies using rats were performed. Results : Some proposed design changes were not implemented, or limitations on their use were established. Most study results, however, were similar to those previously reported in the scientific literature for design changes in cigarette construction. Conclusion : The studies reported in the series of publication demonstrate that our testing approach is feasible for evaluation of cigarette component and manufacturing process changes.